(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2025)
“Soft skills” are intrinsic and interpersonal skills essential for an individual’s development, social activity, personal life, and professional success, regardless of their field of expertise. While professional skills are limited to a specific area of activity, “soft skills” play a crucial role in all aspects of life, from daily routines to professional and social activities.